THU0595 Clinical and therapeutical differences between adults and children in a colombian cohort with inflammatory idiopatic myopathy. (12th June 2018) - Fuentes, R.; Cañola, M.; Diaz-Coronado, J.C.; Rojas-Villarraga, A.; Hernandez-Parra, D.; Perez-Estrada, P.; Salazar-Uribe, J.C.; Pineda-Tamayo, R.
Abstract : Background: Age-related autoimmunity is a key differentiating factor with diverse presentations in different age groups possibly depending on immune regulatory mechanisms. Even patients with the same diagnostic category may have different presentations according to age and other factors. Inflammatory Idiopathic Myopathies (IIM) are not the exception with important clinical and prognostic differences between adults and children. Objectives: To describe the clinical and therapeutical differences between adults and children (younger tahn 18 m years old) in a cohort with IIM Methods: A cross-section retrospective research was done with data collected between 2014 and 2017 from a population diagnosed with IIM according to Peter and Bohan criteria and followed up for at least six months. Statistical association was evaluated by means of Chi-square and Fisher's tests. Results: Out a total of 149 patients, 112 were adults and 37 were children. There was significant difference between the clinical presentation of symmetrical muscle weakness 98% in adults vs 73% in children (p: 0, 0001), Gottron's papules 32% vs 89% (p: 0, 0001), Heliotrope rash 31% vs 62% (p: 0, 0016), Calcinosis cutis 1% vs 37% (p: 0, 0001), Dermatological involvement 47% vs 94% (p: 0, 0001), Myopathic changes in the electromyogram 41% vs 25% (p: 0, 0001), and Myopathy proven biopsy 41% vs 25% (p: 0, 0001). Theraepeutical options showed a significant difference in the use of steroid therapy 93% vs. 84% (p: 0, 045), Methotrexate (58% vs 91% p: 0, 0001), Azatioprine (62% vs 27% p: 0, 0002) and Cloroquine (31% vs 73% p: 0, 0001). Other therapies like Cyclophosphamide (19% vs 5% p: 0, 04) and Inmunoglobulins (23% vs 5% p: 0, 01) were significantly different between adults and children. EMG, electromyogram Conclusions: Several differences in the clinical and therapeutical characeristics were found between adults and children with IIM. Adults had more frequently symmetrical weakness, myopathic changes in EMG and biopsy proven myopathy. In contrast children had higher skin involvement. Calcinosis constituded an important manifestation of IIM in children. These results suggest that paediatric IIM is a distinct sub-phenotype related to the early age at onset and possibly mediated by different immune interplay key factors. Reference: [1] Tansley S, et al. Comparing and contrasting clinical and serological features of juvenile and adult-onset myositis: implications for pathogenesis and outcomes.1040–8711 Copyright!2015Wolters Kluwer Health, Inc Disclosure of Interest: None declared